â€œPENGARUH BAURAN PROMOSI TERHADAP KEPUTUSAN KONSUMEN DALAM MEMILIH KAMAR HOTEL OLLINO GARDEN MALANGâ€ - Negoro, Wignyu; man, Surach (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research aimed to determine the effect of the promotion mix to consumer decision choosing Ollino Garden Malang Hotel rooms simultaneously and partially. Multiple linear regression analysis method used to know how big influence the independent variable (promotion mix) on the dependent variable (purchasing decisions). Based on the results of multiple linear regression analysis is known that the variables are not researched more influence on purchase decisions. Therefore, the promotion mix that has been done by the Ollino Garden Hotel Malang less influence on consumer decisions in choosing Ollino Garden Hotel Malang. Public relations and publicity variables more dominant influence on purchase decisions than the other promotion mix variables. Keywords: Promotion Mix, Decision of the Purchase, Ollino Garden Hotel Malang